Relevance of blood tests before dental implantation - Luca Nagy-Csoma; Dóra Iványi; Péter Kivovics; Orsolya Németh (Hungarian Dental Association, 2021)
Nowadays, dental implantation is increasingly common intervention in dentistry. With the spread of implantations, implantrelated complications are coming into view. Biological complications include peri-implant mucositis and peri-implantitis. General risk factors for peri-implant inflammation include diseases, such as diabetes mellitus and hyperlipidemia. The aim of this study is to examine the efficiency of blood tests before implantation, as a preventive screening method of implantation and its application in the prevention of peri-implant inflammations. 33 patients' dental statuses and blood tests were collected. We analysed our data by Microsoft Excel program (Remond, Washington, USA). The patients' average age was 62,8 (±11). 81,8% of the patients were partial edentulous and 66,7% of partial edentulous patients had periodontal involvement. 21,2% of the observed patients had high blood sugar level, 51,5% of them had elevated blood lipid level. We further examined the association between the prevalence of blood tests' deviation and the prevalence of periodontal involvement. High blood sugar level and periodontal involvement simultaneously occurred in 6,1% and periodontal involvement with increased inflammatory factors were noticed in 21,2% of the patients. Untreated or not properly treated diabetes mellitus is a risk factor of peri-implant inflammation. Hyperlipidemia has negative effects on the local immune response of peri-implant tissues and osseointegration, which influence the long-term success of the implantation. All of the general risk factors with periodontal involvement increased the risk for peri-implant diseases and therefore we have to make risk analysis and regular controls. The blood-test, according to the Department of Community Dentistry, is a suitable and sufficient method to detect general risk factors before implantation.